2017
DOI: 10.4028/www.scientific.net/jbbbe.31.32
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Based Machine Learning Technique to Classify the Different Shoulder Movement of Upper Limb Amputee

Abstract: The wavelet transform is an accurate, efficient and efficacious method to improve the quality of the myoelectric signal. Classification of the signal from upper limb using Surface Electromyogram (SEMG) signal has been the matter of extensive research. Number of methods and algorithms have been described by researchers to classify biomedical signals. The main aim of this paper to extract the different coefficient values from the given SEMG data by using Discrete Wavelet Transform (DWT). Afterward, random forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Absorbing the scalar a T µ into the term a by an appending process, we have Equation (11), with a 0 and x i 0 being (n + 1) dimensional vectors, which ensures that computational complexity is minimised from not centring the data matrix [33,34]. µ is the sample mean vector and x I is the ith data point for a specific class.…”
Section: Spectral Regression Discriminant Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Absorbing the scalar a T µ into the term a by an appending process, we have Equation (11), with a 0 and x i 0 being (n + 1) dimensional vectors, which ensures that computational complexity is minimised from not centring the data matrix [33,34]. µ is the sample mean vector and x I is the ith data point for a specific class.…”
Section: Spectral Regression Discriminant Analysismentioning
confidence: 99%
“…As with Kaur et al. [11], Sharba et al. [4] extracted features from the time‐frequency domain through the wavelet transform and obtained an accuracy of 87% for the case of amputees across seven shoulder motions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study demonstrated the ability to use muscles nearby the shoulder to classify different grips of the arm or hand. Kaur et al 11 carried out a study of shoulder motion classification by using wavelet as a feature extraction with the random forest as a classifier. Their study classified shoulder motions by considering three muscles, namely, pectoralis, trapezius, and teres muscles.…”
Section: Introductionmentioning
confidence: 99%